2014
DOI: 10.1073/pnas.1414335111
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome profiling reveals mosaic genomic origins of modern cultivated barley

Abstract: The domestication of cultivated barley has been used as a model system for studying the origins and early spread of agrarian culture. Our previous results indicated that the Tibetan Plateau and its vicinity is one of the centers of domestication of cultivated barley. Here we reveal multiple origins of domesticated barley using transcriptome profiling of cultivated and wild-barley genotypes. Approximately 48-Gb of clean transcript sequences in 12 Hordeum spontaneum and 9 Hordeum vulgare accessions were generate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
69
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(83 citation statements)
references
References 54 publications
11
69
0
1
Order By: Relevance
“…Although the divergences between the Tibetan wild and cultivated barley are evident, they are even closer in comparison with barley accessions from Europe, East Asia, and Israel, which are sequenced by IBSC. This result came from analyses of PCA, STRUCTURE, F st , and cluster and is consistent with that obtained by transcriptome sequencing (12). Therefore, introducing the gene pool of Tibetan wild barley and those from non-Tibetan groups into Tibetan hulless barley may be helpful in widening the genetic background of Tibetan hulless barley.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Although the divergences between the Tibetan wild and cultivated barley are evident, they are even closer in comparison with barley accessions from Europe, East Asia, and Israel, which are sequenced by IBSC. This result came from analyses of PCA, STRUCTURE, F st , and cluster and is consistent with that obtained by transcriptome sequencing (12). Therefore, introducing the gene pool of Tibetan wild barley and those from non-Tibetan groups into Tibetan hulless barley may be helpful in widening the genetic background of Tibetan hulless barley.…”
Section: Discussionsupporting
confidence: 84%
“…nudum), with naked caryopsis, is mainly cultivated in Tibet and its vicinity, which is one of the domestication and diversity centers for cultivated barley (12)(13)(14)(15)(16). The adaptation to extreme environmental conditions in high altitudes made it the staple food for Tibetans beginning at least 3,500-4,000 years ago (17,18).…”
mentioning
confidence: 99%
“…These results provided evidence that the SNP T643A might cause a loss of function of Nud and that the middle motif might be essential for function. Dai et al (2014) found that hulless barley in Tibet differed from modern cultivated barley at the genomic level and it probably existed in an early stage of domestication. Our findings in the present study provide evidence for a new origin of naked barley in Tibet and support the above viewpoint.…”
Section: Discussionmentioning
confidence: 99%
“…RNA quantity and quality check, library construction, and sequencing were performed as described by Dai et al (2014) and Wang et al (2016). The TruSeq RNA sample preparation kit (Illumina) was used to construct the library following the manufacturer's instructions.…”
Section: Rna-seqmentioning
confidence: 99%